Erotomania: historical-epistemological review and analysis of a case study - Barrio, María Laura; Cuerda, María Lourdes; Estivariz Barilati, Bernardita; Lago, Hernán Eduardo; Lipszyc, Lucila; Vega Poggi, Ana Laura (Revista del Hospital Italiano de Buenos Aires, 2015)
In this paper we analyze the erotomanic concept, focusing on the studies of De Clerambault, who is the main reference in the issue, and a brief analysis of his predecessors. Then, we present a clinical case and analyze it in the light of such contributions
Keywords: delirium; psychosis; erotomanic